2006
DOI: 10.1001/archsurg.141.5.468
|View full text |Cite
|
Sign up to set email alerts
|

Whole Body Imaging in Blunt Multisystem Trauma Patients Without Obvious Signs of Injury

Abstract: Hypothesis: The use of liberal whole body imaging (pan scan) in patients based on mechanism is warranted, even in evaluable patients with no obvious signs of chest or abdominal injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
189
0
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 325 publications
(208 citation statements)
references
References 36 publications
6
189
0
6
Order By: Relevance
“…Many authorities and centers have promoted and adopted protocols of wholebody CT (pan-scan) in polytrauma victims, and a selective chest CT decision rule must take into account the practical considerations of urgent patient evaluation without multiple trips to the CT scanner. 21,22 Nonetheless, we believe that a decision rule of simple criteria can rapidly and safely identify those non-critically injured patients who would benefit from omission of the chest CT portion of these pan-scans (patients who have normal CXRs and a very low risk of clinically significant thoracic injury). Pinette et al 23 have noted that normal findings on CXR and abdominal CT are sufficient to rule out most significant thoracic injuries in blunt trauma patients, especially those who have minor trauma mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Many authorities and centers have promoted and adopted protocols of wholebody CT (pan-scan) in polytrauma victims, and a selective chest CT decision rule must take into account the practical considerations of urgent patient evaluation without multiple trips to the CT scanner. 21,22 Nonetheless, we believe that a decision rule of simple criteria can rapidly and safely identify those non-critically injured patients who would benefit from omission of the chest CT portion of these pan-scans (patients who have normal CXRs and a very low risk of clinically significant thoracic injury). Pinette et al 23 have noted that normal findings on CXR and abdominal CT are sufficient to rule out most significant thoracic injuries in blunt trauma patients, especially those who have minor trauma mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…[11,[21][22][23][24] Selective utilization of CT scanning has been advocated for due to radiation exposure and cost. [22][23][24] However, it has been reported that the treatment plan was changed in 6.4% of cases due to diagnoses determined from CT imaging.…”
Section: Discussionmentioning
confidence: 99%
“…In the developed nations, such as the USA, Japan, and the European countries, whole body CT scans have become widely used in the management of blunt trauma patients. (10)(11)(12)(13)(14) Computed tomography has many advantages as a diagnostic tools, including short examination time, repeatability, reliability, and convenience, leading to an increasing the number of CT examinations. The Health Insurance Review and Assessment Service in Korea also reported that the total number of CT scans has more than doubled from 2003 to 2007.…”
Section: Discussionmentioning
confidence: 99%